Utility of Cell Block Versus Conventional Smear Method in the Cytodiagnosis of Ascitic Fluids - Syed Qaiser Husain Nevi, Razia Tariq, Anwar Ali Jamafi, Riaz Ahmed Qazi (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2013)
Objective: To evaluate the utility of cell block (CB) versus conventional smears (CS) technique in the cytological diagnosis of peritoneal effusions. Place and Duration: Prospective study conducted in the departments of Pathology, Gynae & Obs and Medicine, Peoples University of Medical & Health Sciences, Nawabshah, Shaheed Benazeerabad. during January 2013 to April 2013. Patients and Methods: Total 92 cases of peritoneal effusions were included in this study. The patients were divided into eight groups according to their age. 10 ml of fresh peritoneal fluid was obtained from each patient and divided into two halves in order to evaluate the comparative study by CS and CB methods. Results: Out of 92 samples, on conventional smear examination 83 cases were diagnosed as reactive effusions. while on cell block method the majority (80) cases were confirmed as reactive, one case of tuberculous ascitis and two cases of bacterial infection were confirmed on CB method as malignant. Majority of effusions were diagnosed in order of frequency as a result of c irrhosis, tuberculosis and CCF. In malignant lesions by CS method, 4 cases were diagnosed as suspected and 5 cases as malignant effusions. In CB method the suspected cases were confirmed as malignant while 3 more cases were diagnosed as malignant. All the 12 malignant cases were confirmed on histopathology. The majority of malignancies were detected from ovaries and GIT. Conclusion: In comparison to conventional smear method the cell block method provides high cellularity, better morphological features and architectural patterns, and is more sensitive and simpler method for cytodiagnosis having diagnostic accuracy equal to histopathology.